FDI inflows and domestic interest rate nexus in Nigeria: A new look at the mundell-flemming hypothesis - Ogwuru, Hycenth Richard Oguejiofoalu; Nzeh, Innocent Chile; Emele, Austine Chijioke; Onyenze, Justice Ndubueze; Ekainsai, Zion Stephen (Journal of Economics and Business Letters, 2025)
The relevance of FDI to an economy has led to an avalanche of studies investigating its link with other macroeconomic variables. One such variable that has been discussed extensively in the literature is the domestic interest rate. The link between FDI inflows and interest has been emphasized by the Mundell-Flemming framework, and in recent times, some scholars have contended that FDI inflows exert a downward influence on domestic interest rates. This study seeks to provide empirical evidence for the latter claim by examining the impact of FDI inflows on interest rates in Nigeria. The study used an annual series ranging from 1981-2022 to and under the ARDL framework. The findings reveal that in both the short and long runs, FDI inflows have a negative and significant impact on the real interest rate. This outcome has implications for the implementation of monetary policy in Nigeria. Although a fall in the interest rate is necessary, it could adversely impact the inflation-targeting objective of the monetary authorities. Therefore, the choice of allowing much inflow of FDI into the country should be weighed against the inflationary impact they portend.